A Blueprint for an Emissions Trading System in Bangladesh: Lessons from Global Precedents - Anan, Sabit Ibtisam; Debbie Hopkins (Indonesian Journal Publisher, 2025)
This study designs a blueprint for an Emissions Trading System (ETS) in Bangladesh through comparative analysis of six global systems: the EU ETS, US SO₂ Program, China Regional Pilots, Mexico ETS, Korea ETS, and California Cap-and-Trade. The research evaluates mechanisms for cap setting, allocation, sectoral coverage, and MRV frameworks to identify optimal design elements. My findings indicate that a phased implementation targeting high-emission industries with output-based allocation alongside inter-temporal and inter-spatial trading would be best for balancing emission reduction with economic growth in Bangladesh. The proposed framework offers policymakers a viable pathway to decarbonization while maintaining industrial competitiveness, while also suggesting pathways of future research to predict environmental and economic impacts.